Seductive Atmospheres, Conflicting Symbols: Religious Landmark Buildings in Diverse Societies - Steets, Silke (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2017)
Informed by the sociology of knowledge, this paper understands buildings as “material objectivations” that continuously “act back” upon their users. It examines the following question: Why are the discussions about constructing new (religious) landmark buildings, or the rebuilding of historical ones, so emotionally charged? Using the debate about a proposed golden cross on top of the reconstruction of the Prussian City Palace in Berlin as a starting point, this article studies buildings on two levels: the level of bodily experience, on which they unfold their seductive features, and the level of – often conflicting – symbolic inscription. The analysis shows that religious landmark buildings, such as churches or mosques, use specific means of expression to stimulate the experience of the “numinous.” As a result, they are often loaded with strong emotions and feelings of belonging or dis-belonging. As religious communities increasingly become fragmented in diverse societies, symbolic recognition in landmark projects appears to be a deeply political concern.